2012
DOI: 10.1155/2012/371487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aromatic Boronic Acids as Ligands for Measuring Diabetes Markers on Carbon Nanotube Field-Effect Transistors

Abstract: Biomolecular detections performed on carbon nanotube field-effect transistors (CNT-FETs) frequently use reactive pyrenes as an anchor to tether bioactive ligands to the hydrophobic nanotubes. In this paper, we explore the possibility of directly using bioactive aromatic compounds themselves as CNT-FET ligands. This would be an efficient way to functionalize CNT-FETs since many aromatic compounds bind avidly to nanotubes, and it would also ensure that ligand-binding molecules would be brought in close proximity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The results shown in Figure 3 demonstrate a bell-shaped response curve of E. coli binding to different concentrations of the antibody, with an optimum antibody coating concentration of around 0.5 nM. Previously, we observed a bell-shaped impedance curve in our study of binding of glycated human serum albumin to hydrophobic boronic acid compounds titrated onto CNT-FET circuits, demonstrating the importance of coating concentrations of the capture moieties for maximal ligand signal [15]. Additionally, a bell-shaped response was also observed titrating pyrene-hydrazide-labeled polyclonal antibodies to human IgG (data not shown).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The results shown in Figure 3 demonstrate a bell-shaped response curve of E. coli binding to different concentrations of the antibody, with an optimum antibody coating concentration of around 0.5 nM. Previously, we observed a bell-shaped impedance curve in our study of binding of glycated human serum albumin to hydrophobic boronic acid compounds titrated onto CNT-FET circuits, demonstrating the importance of coating concentrations of the capture moieties for maximal ligand signal [15]. Additionally, a bell-shaped response was also observed titrating pyrene-hydrazide-labeled polyclonal antibodies to human IgG (data not shown).…”
Section: Resultssupporting
confidence: 56%
“…We have used this system to measure serum insulin-like growth factor-1 (IGF-1) in a preclinical mouse model of human Brca1-related breast cancer using immobilized antibodies [14]. Recently, we expanded the repertoire of the CNT-FETs by using small hydrophobic boronic acid compounds to measure glycated human serum albumin, which is a marker for diabetes [15]. One of our goals is to develop this technology to measure multiple biomarkers in real time and to reach these goals we need to adopt and utilize established methodologies, including antibody-based detection.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have shown that SWCNT-FET can be utilized to measure many biological molecules including IGF-1 [43], glycated human serum albumin [44] and hemorrhagic E coli [45]. In the present study we examine the interactions of A40 and Aβ42 peptides with SWCNTs immobilized on silica wafers.…”
Section: Introductionmentioning
confidence: 97%
“…The chromatography samples were applied to the field-effect transistor (FET) circuits according to the procedures of Fuzbien Technology Institute [28][29] to determine semiconductor activity. [30].…”
Section: Introductionmentioning
confidence: 99%